Recomendações funcionais para a descrição de materiais raros em ambientes digitais na perspectiva das tecnologias e princípios Linked Data - Cunha, Gabriela Aparecida da (Universidade Federal de São Carlos, 2025)
The digitization of rare cultural heritage materials requires more than simple visual reproduction. It is essential that digitization occurs simultaneously with a detailed description of the object, including data on its production, provenance, and trajectory, ensuring the preservation of its context and historical relevance. Thus, the question arises: how has the description of rare materials in digital environments with Linked Data characteristics been discussed in the scientific literature of Information Science? The objective is to investigate initiatives for describing rare materials in digital environments from the perspective of Linked Data in the scientific literature of Information Science, in order to: a) analyze and present the state of the art on the description of rare materials in digital environments with Linked Data characteristics; b) present the standards for describing rare materials and identify their characteristics; c) map the standards, instruments, and initiatives for describing rare materials and their characteristics; d) present and analyze cases of description of rare materials in digital environments with Linked Data characteristics; e) identify similarities and differences in the structuring, representation, and description of rare materials in digital environments; and f) propose recommendations for the description of rare materials with Linked Data characteristics. The methodology used comprised a Systematic Literature Review and an empirical study. As a result, with the aim of studying the cases, initiatives, and instruments identified in the corpus in question, five general categories were established: Models for the representation and organization of bibliographic and cultural data, Ecosystem of tools and projects for data, Cataloging Tools and Standards, Semantic Resources, Spectrum of Metadata Schemas. The research analyzed 29 articles and identified 18 practical cases that demonstrated the conversion of traditional metadata (such as MARC) to semantic models (such as BIBFRAME) and its enrichment through connection with external controlled vocabularies. Recommendations were proposed for the description of rare materials, suggesting the adoption of flexible models (BIBFRAME), open vocabularies, and Web standards (such as JSON-LD and IIIF) to ensure interoperability and access to cultural heritage.
Functional recommendations for describing rare materials in digital environments from the perspective of Linked Data technologies and principles
Keywords: Catalogação descritiva; Materiais raros; Ambientes digitais; Bibliotecas digitais; Linked Data; Revisão sistemática da literatura; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO::BIBLIOTECONOMIA; 4. Educação de Qualidade